Analysis of the impacts of health service closure policy on Indonesian nursing during COVID-19 pandemic: A literature review - Casman, Casman; Indah Pertiwi, Retno; Chandra, Muhammad; Mahardika, Putri; Fahmi, Ismail; Fitria Utami, Ayu; Nur Rohmah, Ulfa (The Journal of Palembang Nursing Studies, 2023)
Background: The COVID-19 pandemic has been over yet; one of the effects of this pandemic is plenty of hospitals in Indonesia have been applying for temporary health service closure. Objective: This study aimed to analyse the effect of health service closure during the COVID-19 pandemic. Design: Simple study literature is the method for this study. Data Sources: This study used two different search processes. The first search process came from online news platforms (detik.com, kompas.com, and okezone.com), which used a combination of the words “COVID-19”, “emergency room”, “hospital”, and “closed” during November 2020. The second search was from the database (CINAHL, ProQuest, ScienceDirect, PubMed, SpringerLink, and Wiley Online). Review Methods: The guidelines of the second search used Preferred Reporting Items for Systematic Review and Meta-Analysis. Both searching processes applied COVID-19 and hospital closed or emergency department closed as the keywords from November 2020-January 2021. Results: The first finding showed more than 300 news about health service closure, and the second showed 13 selected articles. There were 42 health service unit closures from 16 provinces in Indonesia. These closures had disadvantages effect for patients, nursing care and nursing education side. Conclusions: Total or partial health service closure could be happened due to increased patient capacity, delays in the treatment of the patient, many nurses getting infected by COVID-19, and nursing students cannot practice directly. Therefore, this issue needs innovative solutions to keep the nursing student placement going well by considering safety for the patient, nurses, nursing students, and trainer/ facilitator.